The relationship between usage of ICT and student achievement: Case study of students in DPP Bank Rakyat, UUM - Iteng, Rosman; Wan Mustapha, Wan Khairi (2015)
The study was conducted on the relationship between usage of ICT and student achievement in learning session at the university among the students.ICT is a useful tool in efforts to make the learning process more relevant and understandable to students.In the context of ICT, learning can be carried out via Facebook, WhatsApp and even E-learning.The level of achievement will be measured by the grade and the feedback obtained.Accordingly, this paper discusses the ICT resources that are often used by students and also to measure the level of understanding students in the learning.A total of 40 students representing University Utara Malaysia final semester students were chosen as respondents for this study.Survey forms were used as a research instrument.Information for this study were examined utilizing the Statistical Package for Social Sciences (SPSS) Version 11.0 for Windows. Based on a survey conducted through correlation methods, the usage of ICT by students showed negative correlation.This shows that the usage of ICT does not affect the achievement of students.